Long-term Evaluation of the Effect of Platelet-rich Fibrin on Cartilage Tissue Regeneration: An Animal Model Study - Goljanian Tabrizi, Ali; Hashemi , Hamzeh; Mohsenifar , Zhaleh; Bohlouli, Mahboubeh (Regeneration, Reconstruction & Restoration (Triple R), 2021)
Introduction: Autologous cartilage graft in rhinoplasty is associated with common challenges, such as resorption, inflammation, and bone metaplasia. This study aimed to assess platelet-rich fibrin's long-term effect, as a superphysiological source of biomolecules, on cartilage regeneration in an animal model. Material and Methods: Cartilage and fascia were excised autologously from the ear and leg of thirty-three Wistar rats. They then transplanted with cartilage alone (control group), cartilage wrapped with fascia (fascia group), and cartilage wrapped with PRF (fibrin group) autologously and subcutaneously. Result: The histological results demonstrated no significant difference in chondrocyte viability, fibrosis, and resorption between three groups after six months. However, other parameters, including calcification, bone metaplasia, infection, and basophilia, were lower in the fibrin group. Conclusion: This study concluded that PRF could be an appropriate autologous cell source for cartilage regeneration and nasal augmentation in the long term.